Heterotrophic phytoplankton of the Black Sea: species composition and spatial distribution. - Zav'yalova, T A; Mikaelyan, A S (PANGAEA, 1997)
Species composition and spatial distribution of heterotrophic algae were studied in the Black Sea in autumn 1992. Total phytoplankton biomass varied during that period from 8 to 30 g/m**2. Autotrophic species Ceratium fusus and Rhizosolenia calcar-avis dominated. The list of species of heterotrophic dinoflagellates consisted of 14 species. Species diversity in the eastern part of the sea was higher as compared with its western part. Heterotrophic phytoplankton amounted up to 13% of the total phytoplankton biomass. Species Pronoctiluca pelagica and Ceratium fusus contributed most of all to biomass of heterotrophic component of the phytocenosis (12-93 and 1.7-60% respectively). Population of C. fusus consisted of both autotrophic and heterotrophic cells. Cells of chlorophyll-containing C. fusus dominated in zones of the western and the eastern upwellings. Heterotrophic cells dominated in the center of the sea and in the eastern part of the Main Black Sea current. Similarity and quantitative relations between distributions of heterotrophic P. pelagica and of chlorophyll-containing C. fusus were recognized.
(Table 1) Parameters of the upper mixed layer of the Black Sea in October 1992
Keywords: Archive of Ocean Data; ARCOD; Black Sea; Date/Time of event; Depth of pycnocline; Depth of Secchi Disk; Mixed layer, thickness; Nitrate and Nitrite; Phosphate; Secchi disc; Silicon; Temperature, water; Titration; TRANS150; Transparent bottle 150L; Vy26-3793; Vy26-3794; Vy26-3795; Vy26-3797; Vy26-3801; Vy26-3804; Vy26-3818; Vy26-3819; Vy26-3822; Vy26-3826